From stories to numbers: development of folktale-based instructional materials in mathematics - Cherry Joy B. Demingoy; Roberto G. Sagge Jr.; Tedric Dave E. Senosa; Renato V. Herrera Jr.; Salvador P. Bacio, Jr.; Julynn J. Rico; Julie Gay B. Quidato; Rosemarie G. Felimon; Franz Ian D. Solomon (International Journal of Evaluation and Research in Education (IJERE), 2026)
Persistent learning gaps and the scarcity of culturally anchored resources continue to challenge Grade 7 mathematics instruction in rural public schools in the Philippines, particularly under the MATATAG curriculum. This study developed and evaluated a folktale-based instructional material that integrates local Panay folktales with target Grade 7 competencies in measurement and geometry and number and algebra to support meaningful, context-rich learning. Using a Type I developmental research design guided by analysis, design, development, implementation, and evaluation (ADDIE) model and anchored on social constructivism and attention, relevance, confidence, and satisfaction (ARCS) motivational framework, the material was produced through competency mapping, story-task scripting, iterative expert review, and pilot implementation. Participants included 25 Grade 7 mathematics teachers who identified suitable competencies, 10 content and pedagogy experts who validated the material, and 66 Grade 7 learners from four public secondary schools who evaluated usability and learning support. Acceptability was measured using adapted expert and learner evaluation forms with a 5-point scale and summarized using descriptive statistics. Results indicated an overall rating of highly acceptable. Format and design received the highest evaluation, followed by organization and presentation and learning objectives; content and assessment were rated acceptable, highlighting specific areas for refinement. These findings suggest that embedding mathematical concepts in culturally familiar narratives can improve perceived clarity, engagement, and task coherence while maintaining alignment with curriculum standards. The study contributes a replicable, culturally responsive development process and a ready-to-adapt set of story-based math tasks for teachers in similar contexts. Future work may examine learning gains through quasi-experimental implementation and explore digital adaptations to broaden access and interactivity.